Indhuppu (rock salt) in Siddita aspect: a review - Sripandurangana, R.; Sounthararajan, K. (Gari Research Symposium 2021, 2021)
Siddha medical system is known as one of the Indigenous medical system which is practiced in Northern and Eastern part of Sri Lanka and Southern India. Siddha system of medicine is predicted on "tridhosa theory (vata, pitta, kapha)" and "Panchaboothas theory (Five elements- earth, water, fire, air, space)". According to the siddha classification, the thathu sarakkugal (minerals), rock salt is considered as a major raw material under 25 Karasaram(salts). The indhuppu is mostly used for medicine preparation which is mentioned in Siddha literatures. Those medicines are mostly used as tridhosa samana. The aim of this study was to review on the rock salt in Siddha aspect. Objectives of this study is to identify the organoleptic character. contents of five elements. pharmacological properties. Literature study was collected in databases and scientific journals with Siddha text books from September to December of 2020. Data was analyzed and compiled using tables and graphs. Rock salt has sweet (earth and water) and salt (water and fire) taste. It has laxative, purgative, carminative, digestive. diuretic. stomachic, liver tonic, anodyne. emetic, dyspepsia. Rock salt can also help promote tone of tissues. weight and digestion, enhances complexion and vigor, stimulate appetite, liquefaction of phlegm, relieves constipation, cleanses the srotas and perspiration. so, it promotes a healthy metabolism within the body, introducing rock salt to the body allows for increased water absorption within the digestive system and surrounding organs. This literature review provides useful documented evidence en indhuppu.
Keywords: Siddha Medicine; Indhuppu; Tridhosa; Five elements